THE EFFECT OF JOB SATISFACTION AND INNOVATIVE BEHAVIOR ON LECTURER PERFORMANCE (CASE STUDY AT MUHAMMADIYAH UNIVERSITY IN SOUTHEAST SULAWESI) - Abdul Hamid; Disman Disman; Tjutju Yuniarsih (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Performance is an important determinant in the life of organizations including for-profit and non-profit organizations. The performance of lecturers in universities is very important to realize goals, including creating quality graduates and building competitiveness that promises continuous progress for all stakeholders involved. Therefore, it is very important to examine the effect of job satisfaction, innovative behavior on lecturer performance. This study aims to find out and analyze and examine how much influence job satisfaction and innovative behavior have on lecturer performance. This research also seeks to find relevant models of work satisfaction and innovative behaviors that affect lecturer performance. In this study, a questionnaire with a likert scale was used to collect data from 350 lecturers, whose sampling was determined using the Slovin method so that the number of samples in this study amounted to 78 lecturers. The results showed that job satisfaction with a T value of 5,897 and a significant value of 0.000 so that job satisfaction had a significant effect on the performance of lecturers at the University of Muhammadiyah Kendari and Muhammadiyah Buton University, then innovative behavior with a T value of 4,901 and a significant value of 0.000 so that innovative behavior had a positive and significant effect on the performance of lecturers at the University of Muhammadiyah Kendari and the University of Muhammadiyah Buton.